(untitled) (Homiletic, 2015)
This essay builds on the author’s experiences hearing preaching while growing up in the Caribbean. The author offers an acute critique of the traditional sermon, affirming that “deductive preaching is colonial preaching.” Acknowledging the contradictions common in the Caribbean, where the colonial and the postcolonial clash every day, Jiménez calls for the development of a postcolonial Caribbean homiletic.